Remarks on linguistic neutrality in the media: the Educ.ar Manuals of Style (2009-2015) (Anclajes, 2019)
This paper analyzes the significance of the expression “argentino neutro” [neutral Argentinian], used from 2009 to 2015 in official documents on the education portal Educ.ar and on the Ministry of Education’s various TV channels (“Encuentro,” “Pakapaka” and “DeporTV”). By examining style manuals in detail from Encuentro and Pakapaka, corresponding to the years 2012-2015, we will attempt to show that these documents construct a linguistic model alternate to the various attempts at Spanish language unification, in particular “Panhispanism” or so-called “neutral Spanish.” Moreover, this alternative linguistic model was consistently reflected in the Ministry of Education’s television programming, which exhibited a much more diverse linguistic representation in Argentinian media than usual.
Keywords: Linguistic policies; Spanish; national language; Argentina; media